(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2022)
This essay aims to investigate Alice Ceresa’s collaboration with the radio and focuses on the audio documents which have been produced within this context in the 1970s (today preserved in the archives of the Radio della Svizzera Italiana, RSI). Sometimes, Ceresa did not publish literary texts which previously had been read on radio. Instead, these texts have been published only posthumously, as in case of the Piccolo dizionario dell’inuguaglianza femminile. These audio documents are relevant witnesses of the first dissemination of these texts. They have to be considered in the study of the textual tradition of these literary works in the preparatory phase of a scholarly edition of Ceresa’s Œuvre. Their function will be shown by examining, in particular, the compositional process of the Piccolo dizionario.